Analysis of Factors Influencing Compliance with Radiation Safety Implementation in the Operating Room in the Use of C-Arm at Hospital X, Padang - Oktavia Puspita Sari; Santa Mareta; Yori Rahmadianti (Journal of Public Health Indonesian, 2026)
The use of C-Arm in the operating room is one of the radiological technologies that greatly assists doctors in performing surgical procedures in real time. The C-Arm produces X-ray radiation that allows visualization of anatomical structures during surgery. However, radiation exposure from the use of a C-Arm can pose risks to healthcare workers in the operating room, such as doctors, nurses, and radiographers, if not accompanied by proper radiation safety practices. Compliance with the use of personal protective equipment (PPE) in the operating room during the use of C-Arm devices at Hospital X Padang in 2024 is expected to serve as a basis for improving the implementation of radiation safety for healthcare workers. Based on observations, it was found that not all operating room staff used radiation protective equipment according to regulations, even though the potential radiation hazards from the C-Arm in the operating room are quite significant. This may result in increased radiation doses received by workers present during the operation of the C-Arm. The purpose of this study was to determine the factors influencing non-compliance among operating room staff during the use of the C-Arm. This quantitative study used a cross-sectional design, with the population consisting of all operating room staff at Siti Rahmah Hospital, using total sampling with 32 respondents. The research instrument used was a questionnaire. After all data were collected, the data were processed and analyzed using the Spearman test. Out of 32 respondents, 18 were male (56.2%) and 14 were female (43.8%). Based on age categories, 24 respondents (75%) were aged 20–30 years, 4 respondents (12.5%) were aged 30–40 years, and 4 respondents (12.5%) were aged 40–50 years. Based on years of service, 24 respondents (75.0%) had 0–5 years of experience, 4 respondents (12.5%) had 5–10 years, and 4 respondents (12.5%) had 10–15 years of experience. Regarding education level, 20 respondents (62.5%) held a D3 diploma and 12 respondents (37.5%) held a D4 diploma. In terms of knowledge level, 8 respondents (25.0%) had low knowledge, 7 respondents (21.9%) had moderate knowledge, and 17 respondents (53.1%) had good knowledge. Regarding attitudes, 15 respondents (46.9%) had poor attitudes, while 17 respondents (53.1%) had good attitudes. The availability of radiation protection facilities for operating room staff showed that 15 respondents (46.9%) reported inadequate availability, while 17 respondents (53.1%) reported adequate availability. There was a relationship between age, years of service, education level, knowledge level, attitudes, and the availability of facilities and infrastructure with compliance in implementing radiation safety. However, there was no relationship between gender and compliance with radiation safety practices.